2001
DOI: 10.1007/s004210000330
|View full text |Cite
|
Sign up to set email alerts
|

Changes in muscle size, architecture, and neural activation after 20 days of bed rest with and without resistance exercise

Abstract: Nine healthy men carried out head-down bed rest (BR) for 20 days. five subjects (TR) performed isometric, bilateral leg extension exercise every day, while the other four (NT) did not. Before and after BR, maximal isometric knee extension force was measured. Neural activation was assessed using a supramaximal twitch interpolated over voluntary contraction. From a series cross-sectional magnetic resonance imaging scans of the thigh, physiological cross-sectional areas (PCSA) of the quadriceps muscles were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
160
4
11

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(196 citation statements)
references
References 22 publications
21
160
4
11
Order By: Relevance
“…Bed rest studies have shown a decrease in the root mean square (RMS) of EMG of 6.5% after 20 days (Kawakami et al, 2001) and 19% after 42 days (Edgerton et al, 2001). Nevertheless, the contribution of reduced neural drive to the loss of muscle strength associated with disuse seems still an unresolved issue as several studies showed no change in maximal EMG activity in both vastus lateralis (de Boer et al, 2007) and plantar flexor muscles (Seynnes et al) after ULLS, whilst others (Clark et al 2006a) showed a 30% decrease in compound muscle action potential (CMAP).…”
Section: Introductionmentioning
confidence: 99%
“…Bed rest studies have shown a decrease in the root mean square (RMS) of EMG of 6.5% after 20 days (Kawakami et al, 2001) and 19% after 42 days (Edgerton et al, 2001). Nevertheless, the contribution of reduced neural drive to the loss of muscle strength associated with disuse seems still an unresolved issue as several studies showed no change in maximal EMG activity in both vastus lateralis (de Boer et al, 2007) and plantar flexor muscles (Seynnes et al) after ULLS, whilst others (Clark et al 2006a) showed a 30% decrease in compound muscle action potential (CMAP).…”
Section: Introductionmentioning
confidence: 99%
“…O VL é um músculo penado, superficial e de arquitetura pouco complexa (BLAZEVICH 2007a). Dessa forma, é frequentemente analisado em estudos com US (KAWAKAMI et al, 2001;KUBO et al, 2003;REEVES et al, 2004;KAWAKAMI, et al, 2006;MAGANARIS et al, 2006; BLAZEVICH et al, 2007a;BLAZEVICH et al, 2007b; BRANCACCIO et al, 2008;DE BOER et al, 2008;REEVES et al, 2009; BLAZEVICH et al, 2009).…”
Section: Doi: Confiabilidade Do Vasto Lateralunclassified
“…O músculo analisado pertencia ao dimídio direito. Primeiramente, foi medido o comprimento da coxa (distância entre o trocânter maior do fêmur a interlinha articular do joelho), e em seguida, marcada a região de 50% deste comprimento (ABE et al, 2001;KAWAKAMI et al, 2001;KAWAKAMI et al, 2006; BLAZEVICH et al, 2007a; BLAZEVICH et al, 2009), lateralmente à coxa.…”
Section: Procedimentounclassified
See 1 more Smart Citation
“…One must consider the benefits of exercise, the benefits of exercise during pregnancy, the possible detrimental effects of activity restriction, and the feasibility of exercising in a hospital setting before incorporating a bedrest-exercise intervention program for activity restricted antenatal women. The benefits of incorporating a bedrest-exercise program have yet to be fully investigated in the antepartum hospitalized population, but are well documented in the non pregnant population [20][21][22][23][24]. The first study was conducted in 1992, by Mayberry and colleges, in order to assess the short-term effects of controlled bed-rested exercise on uterine activity of women diagnosed with preterm labour [25].…”
Section: Introductionmentioning
confidence: 99%